Analisis Risiko Beban Kerja dengan Metode NIOSH Lifting Equation dan Rapid Entire Body Assessment pada Aktivitas Dumping Aditif di PT X - Dani Hermawan; Agustina Christiani (Universitas Pelita Harapan, 2026)
Additive dumping activities at PT X are characterized by manual, repetitive lifting of sacks and frequent bending postures, which may increase the risk of developing Musculoskeletal Disorders (MSDs). Based on the results of the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), the predominant area of reported discomfort was the lower back. This study aimed to evaluate workload risks using the NIOSH Lifting Equation and the Rapid Entire Body Assessment. The initial assessment indicated a high-risk lifting task, with a Composite Lifting Index of 1.1307, exceeding the recommended threshold of 1.00, and a REBA score of 10, signifying a high level of risk. An ergonomic intervention involving the implementation of a Manual Hydraulic Stacker Forklift was proposed to elevate the initial load to waist height, thereby improving worker posture. Simulation results of the proposed intervention demonstrated a reduction in the lifting index to 0.88 and a substantial decrease in the REBA score to 3, corresponding to a low-risk category. These findings underscore the effectiveness of material handling equipment in mitigating musculoskeletal risk factors.